Homicidal Death By Crude Bomb Explosion: A Case Report With Forensic Patho-Mechanical Insights (Journal of Forensic Medicine & Toxicology, 2026)
Background: Crude bombs are homemade explosive devices created from inexpensive and easily accessible materials like glass fragments, jute fibers, stones, iron nails, etc. They serve as a substitute for costly explosives. Crude bomb explosions have complicated medicolegal ramifications that necessitate a thorough comprehension of the patho-mechanics of the injuries sustained. The patho-mechanics of damage caused by homicidal crude bomb blasts is an uncommon and emerging entity, the knowledge of which is essential to answer the medicolegal query in these cases. Case Presentation: In a small village in eastern India, a crude bomb was thrown at a middle-aged man during an argu ment, resulting in an explosion that caused bodily injuries. The patho-mechanics of the injuries held to reach to the conclusion regarding event reconstruction, the victim’s proximity to the explosive material at the moment of detonation, alongside comprehensive evidence collection, which is presented in this paper. Conclusion: This study shows that forensic teams must be extremely precise when examining injuries and gathering evidence. If they aren’t, a crime like murder or terrorism could easily be mistaken for an accident. Careful evidence col lection is key for police and security agencies to find the guilty parties and stop similar events.
Keywords: Blast injuries; Forensic Pathology; Crude Bombs; Homicide; Case Report